Fcε receptor II/CD23+ lymphocytes in atopic dermatitis. III. Aberrant control in the in vitro expression of FcεRII/CD23 on peripheral blood T cells in atopic dermatitis - SAKAMOTO, T.; NAKAYAMA, F.; TAMAMORI, T.; TAKIGAWA, M. (Clinical and experimental immunology, 1992)
SUMMARY In vitro FcεRII expression was examined in patients with atopic dermatitis, those with non‐atopic eczematous dermatitis and normal individuals following stimulation of peripheral blood cells with recombinant IL‐4 (rIL‐4), phytohaemagglutinin (PHA), or PHA plus rIL‐2. At various days cells were stained with MoAbs to human lymphocyte FcεRII and to lymphoid cell‐surface antigens and analysed by flow cytometry, rIL‐4, but not rIL‐2, specifically induced FcεRII on T cells as well as B cells in atopic dermatitis, eczematous dermatitis and normal individual groups. Both atopics and non‐atopics generated comparable proportions of FcεRII+ T cells (Tε cells), whereas the frequency of B cells bearing FcεRII(Bε cells) was significantly higher in patients with extensive atopic dermatitis than in those with mild atopic dermatitis and other subjects. Comparable levels of Tε cells were detected in both atopic and non‐atopic donors following stimulation of peripheral blood cells with PHA or pre‐activation of the cells with PHA plus subsequent incubation with rIL‐2. Whereas both CD8+ and CD4+ subsets were present in Tε cell populations induced specifically by rIL‐4, PHA and PHA plus rIL‐2, patients with atopic dermatitis had a greater tendency for FcεRII expression on CD8+ T cells compared with patients with eczematous dermatitis and normal individuals. Recombinant interferon‐gamma (rIFN‐γ), but not rIFN‐α or prostaglandin E2 (PGE2), suppressed the generation of Tε cells by rIL‐4 in atopics and non‐atopics to the same degree. These results suggest the aberrant control of FcεRII expression on T cells, especially those bearing CD8, in atopic dermatitis.